Innovative Vapor Transport Deposition Technique for Selenium Thin-Film Solar Cell Fabrication - Jie Wang; Fan He; Min Zhang (Nanoenergy Advances)
The recent focus on wide-bandgap absorbers for tandem solar cell configurations and photovoltaic materials with high absorption coefficients for indoor photovoltaics has prompted a renewed interest in selenium. Over the past few years, the efficiency of Se solar cells has improved significantly, bringing the prospect of industrial production closer to reality. This study presents an innovative vapor transport deposition (VTD) technique for the scalable and cost-effective fabrication of Se thin films. The prepared Se thin films were characterized, and the results show that the VTD method is capable of producing dense and well-crystallized Se thin films. Se solar cells with a structure of glass/FTO/TiO2/Se/Au were fabricated to evaluate the impact of substrate temperature on device performance. The optimal performance was achieved on the hot side of the substrate during deposition, with a power conversion efficiency (PCE) of 2.56%. This study provides a promising pathway for the low-cost, high-throughput manufacturing of high-performance Se solar cells, facilitating their potential industrial implementation.